2015
DOI: 10.1002/2015gl064911
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the source of quasiperiodic VLF emissions using ground‐based and Van Allen Probes satellite observations

Abstract: We report on simultaneous spacecraft and ground‐based observations of quasiperiodic VLF emissions and related energetic‐electron dynamics. Quasiperiodic emissions in the frequency range 2–6 kHz were observed during a substorm on 25 January 2013 by Van Allen Probe‐A and a ground‐based station in the Northern Finland. The spacecraft detected the VLF signals near the geomagnetic equator in the night sector at L = 3.0–4.2 when it was inside the plasmasphere. During the satellite motion toward higher latitudes, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
88
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(99 citation statements)
references
References 34 publications
11
88
0
Order By: Relevance
“…Hot (1-50 keV) electron populations with a temperature anisotropy are injected from the plasmasheet during substorms and are believed to provide the necessary free energy source for chorus wave excitation via linear and non-linear processes (e.g., see Andronov and Trakhtengerts 1964;Kennel and Petschek 1966;Cully et al 2011;Titova et al 2015). Recently, Fu et al (2014b) have demonstrated via numerical simulations using measured electron distributions with large enough temperature anisotropies that a low energy (∼ 300 eV) population could drive quasi-electrostatic very oblique upper-band (with ω/Ω ce0 > 0.5) chorus waves while a hotter (> 2 keV) component was simultaneously generating quasi-parallel lower-band (with ω/Ω ce0 < 0.5) chorus waves.…”
Section: Oblique Wave Generationmentioning
confidence: 99%
“…Hot (1-50 keV) electron populations with a temperature anisotropy are injected from the plasmasheet during substorms and are believed to provide the necessary free energy source for chorus wave excitation via linear and non-linear processes (e.g., see Andronov and Trakhtengerts 1964;Kennel and Petschek 1966;Cully et al 2011;Titova et al 2015). Recently, Fu et al (2014b) have demonstrated via numerical simulations using measured electron distributions with large enough temperature anisotropies that a low energy (∼ 300 eV) population could drive quasi-electrostatic very oblique upper-band (with ω/Ω ce0 > 0.5) chorus waves while a hotter (> 2 keV) component was simultaneously generating quasi-parallel lower-band (with ω/Ω ce0 < 0.5) chorus waves.…”
Section: Oblique Wave Generationmentioning
confidence: 99%
“…For example, Nėmec et al (2016) show that the time delay between QP simultaneously detected in space and on the ground is related to azimuthally propagating compressional ultra low frequency waves responsible for the generation of the QP. Although by their nature, conjugated events give us significant information on the generation and propagation of waves, up until now they remain rare with only a handful of documented cases (Martinez-Calderon, 2016;Nėmec et al, 2016;Titova et al, 2015). Manninen et al (2013) and Manninen et al (2014) found that the variations of QP periods, particularly their gradual increment, can be explained by the auto-oscillation regime of the cyclotron instability in the magnetosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Titova et al (2015) reported simultaneous observations of the high-frequency QP emissions, showing similar spectral and frequency features between ground-based VLF receiver at KAN and Van Allen Probe spacecraft located above UK to SouthWest from KAN. The authors concluded that this QP event was generated inside the plasmasphere at much lower L-shells than KAN, but they did not discuss the propagation properties of these emissions.…”
Section: Discussionmentioning
confidence: 99%